Flow Cytometry of the Side Population (SP). Issue 1 (1st April 2013) - Petriz, Jordi
Abstract: The side population (SP) has become an important hallmark for the definition of the stem‐cell compartment, especially for the detection of stem cells and for their physical isolation by fluorescence‐activated cell sorting (FACS). SP cells are CD34 − and were discovered using ultraviolet excitation based on the efflux of Hoechst 33342 (Ho342). Although the method works as originally described, the protocol is difficult for most investigators to perform: first, because the ability to discriminate SP cells is based on the differential retention of Ho342 during a functional assay; second, because of the difficulties in setting the right experimental and acquisition conditions; and third, because analysis of the acquired data requires extensive expertise in flow cytometry to accurately detect the SP events. More recently, a new assay based on the efflux of Vybrant DyeCycle Violet stain (DCV) has been documented to discriminate SP cells. This unit contains many helpful pointers to aid the user in obtaining the best possible results with these assays. Curr. Protoc. Cytom . 64:9.23.1‐9.23.20. © 2013 by John Wiley & Sons, Inc.